DESIGN AND DEVELOPMENT OF HIGH-ACCURACY MACHINE FOR WIRE BENDING - Mustafa F.F.; Hussein O.; Fakhri O.F.; Sabri A.H. (Technology Center, 2023)
The use of a bending machine acquired a high level of importance as a consequence of increasing the level of the industry. This paper aims to develop a more accurate and precise bending machine. The proposed bending machine has achieved brilliant output products, in which three main manufacturing parameters have been examined for the production of an equilateral triangle, which are flange length, bending angle and bending radius. The main point depends on the proposed algorithm, which has been developed based on separating the process, in which the central controller is responsible mainly for controlling the sub-controller, where the sub-controllers are programmed using PID to control the entire mechanisms of feeding and bending separately and ensure that the outcomes of these mechanisms are compatible with the input data from the central controller. Ten different dimensions of an equilateral triangle design sample with ten tries for each dimension (variable flange length, fixed bending angle equals to 60 degrees and bending radius equals to 3 mm) have been selected being produced using the bending machine, and the products have been formed two times. Firstly, using the proposed bending machine, in which the proposed algorithm is applied. Secondly, using the bending machine implemented without applying the proposed algorithm. The results have been compared in terms of error rates with respect to the standard design of products designed using CAD/CAM application. An enhancement has been recorded in terms of product accuracy and precision for the parameters of flange length, bending angle and bending radius. The overall accuracy level reaches up to 98.85228 % for a product manufactured using the proposed machine by applying the proposed algorithm compared with a product made with the machine designed without the proposed algorithm 2020. Faiz F. Mustafa, Omar Hussein Alwan, Osamah F. Fakhri, Ahmed H. Sabri. All Rights Reserved.